Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Sanders, Richard J.; Henson, Stephanie A.; Martin, Adrian P.; Anderson, Tom R.; Bernardello, Raffaele; Enderlein, Peter; Fielding, Sophie; Giering, Sarah L. C.; Hartmann, Manuela; Iversen, Morten; Khatiwala, Samar; Lam, Phyllis; et al. (Frontiers in Marine Science, 2016)
The ocean’s biological carbon pump plays a central role in regulating atmospheric CO2 levels. In particular, the depth at which sinking organic carbon is broken down and respired in the mesopelagic zone is critical, with deeper remineralisation resulting in greater carbon storage. Until recently, however, a balanced budget of the supply and consumption of organic carbon in the mesopelagic had not been constructed in any region of the ocean, and the processes controlling organic carbon turnover are still poorly understood. Large-scale data syntheses suggest that a wide range of factors can influence remineralisation depth including upper-ocean ecological interactions, and interior dissolved oxygen concentration and temperature. However these analyses do not provide a mechanistic understanding of remineralisation, which increases the challenge of appropriately modelling the mesopelagic carbon dynamics. In light of this, the UK Natural Environment Research Council has funded a programme with this mechanistic understanding as its aim, drawing targeted fieldwork right through to implementation of a new parameterisation for mesopelagic remineralisation within an IPCC class global biogeochemical model. The Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS) programme will deliver new insights into the processes of carbon cycling in the mesopelagic zone and how these influence ocean carbon storage. Here we outline the programme’s rationale, its goals, planned fieldwork and modelling activities, with the aim of stimulating international collaboration.